Waktu Skor Pemulihan Bromage 2 dengan Metode Enhanced Recovery After Caesarean Surgery (ERACS) dan Non ERACS di Rumah Sakit Emanuel - Sulistyawati Geraldine Rambu Diki Ridja; Roro Lintang Suryani; Madyo Maryoto; Aris Rahmat (Journal of Educational Innovation and Public Health, 2026)
Cesarean section (CS) is an obstetric surgical procedure whose incidence continues to rise, making it necessary to optimize postoperative recovery to support early mobilization and prevent complications. Most CS procedures are performed under spinal anesthesia, making motor recovery an important indicator assessed using the Bromage score. The ERACS method was developed to accelerate recovery through a multimodal approach. Data from Emanuel Hospital show that out of 223 CS cases, 70 cases used ERACS and 153 cases were non-ERACS; however, data on the time to achieve a Bromage score of 2 for both methods are not yet available. This study aims to determine the profile of the time to achieve a Bromage score of 2 in post-SC patients using the ERACS and non-ERACS methods. This study employed a quantitative descriptive design with a cross-sectional approach involving 55 respondents selected via consecutive sampling. Data were collected through observation until patients reached a Bromage score of 2 and were analyzed using univariate analysis. The results showed that the mean time to achieve a Bromage score of 2 in the ERACS group was 39.00 minutes (15–75 minutes), and in the non-ERACS group, it was 67.50 minutes (30–90 minutes). Respondents were aged 19–43 years, with the majority having an ASA II physical status (96.4%), and the most commonly used anesthetics were bupivacaine (56.4%) and lidocaine-morphine as an adjuvant (43.6%). In conclusion, the ERACS method showed a trend toward faster motor recovery, thereby potentially supporting early mobilization and the development of perioperative care protocols. These findings reinforce the importance of implementing ERACS in anesthetic practice to support early mobilization, serve as a basis for the development of hospital protocols, and open opportunities for further research with analytical designs to strengthen the scientific evidence.